Satellite Communication and Long Distance Education - Hafied Cangara (Universitas Negeri Malang, 2016)
Since Indonesia introduced communication satellite for telecommunication network, the satellite has brought a number of advantages for national development in various areas, such as telephone network, mass media development, business, education, politics, security and national defence as well as regional and international cooperation. In education, satellite communication could be used for long-distance learning as implemented by 13 state universities in eastern parts of Indonesia. It is also possible to develop the Open University System in teaching and learning process, particularly since the internet technology has been intensively used